Pengaruh Ukuran Perusahaan, Solvabilitas, Umur Perusahaan, Opini Auditor, Ukuran Kap, Dan Profitabilitas Terhadap Audit Delay (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Astuti, Nita Dwi; , Fauzan S.E., M.Si., Ak (2017)
This research purposed to know the influence of company size, the age of company, profitability, solvability, size of public accountant, and auditor's opinion towards the audit delay in the index manufacturing company listed on the Indonesia Stock Exchange 2013-2015. This research use secondary data from Indonesia Stock Exchange (IDX) websites. Purposive sampling technique is used in this research and there are 117 samples collected by this technique. Technique of data analysis in this research used multiple linear regression that has previously been fulfilled the classical assumption test. The results showed the solvability and profitability had influence to the audit delay, while the company size, age of company size, auditor's opinion and of public accountant didn't significant influence to the audit delay. Simultaneous significance test concluded that company size, solvability, the age of company, auditor's opinion, size of public accountant, and profitability influences audit delay. Simultaneously, company size, solvability, the age of company, auditor's opinion, size of public accountant, and profitability exhibited significantly effect to the audit delay of manufacturing company listed on Indonesia Stock Exchange 2013-2015. Keywords: company size, the age of company, profitability, solvability, size public accountant, auditor's opinion, audit delay.